Pandemic and The Path To Religious Moderation - Thaufiq Hidayat; Asmawati Asmawati (Universitas Islam Negeri Imam Bonjol Padang, 2022)
The Covid-19 threat continues to grow the life of the human life. It is not this epidemic to be a problem for the way of the Muslim religion. The controversy of Covid-19 earnings has a variety of understanding of the influence on Muslim attitudes in the face of pandemics. It may respond with excessive fear so that it is to dismiss the power of God; others are too manifesting impressed to reject the scientific reality. Therefore, it is necessary to understand the meaning of religious moderation in handling this outbreak. This article analyzes how to actualize religious moderation during a pandemic, from understanding steps to actual steps. The research method used in this paper uses the library research approach formulated by the description method and interpretative analysis related to the issues discussed. The results of this study show there are several roads to actualize the moderate of this pandemic era, among others, balancing theology, obeying the health protocol, strengthening knowledge, taking alerting or controlling emotions, and if it has been declared positively immediately prioritized.Ancaman Covid-19 terus menggerus lini kehidupan umat manusia. Tak pelak juga wabah ini menjadi problem terhadap cara keberagamaan muslim. Kontroversi mewabahnya Covid-19 menimbulkan berbagai sudut pemahaman yang berpengaruh pada sikap muslim dalam menghadapi pandemi. Kiranya ada yang menanggapi dengan rasa takut yang berlebihan sehingga menafikan kekuasaan Tuhan, sebagian lainnya bersikap terlalu menyepelekan terkesan menolak realitas ilmiah. Oleh karena itu, diperlukan sikap dan pemahaman yang mengandung makna moderasi beragama dalam menangani wabah ini. Artikel ini bertujuan untuk menganalisa bagaimana mengaktualisasiakan moderasi beragama di tengah pandemi mulai dari langkah memahami sampai pada langkah nyatanya. Metode penelitian yang digunakan dalam tulisan ini menggunakan pendekatan library research yang diformulasikan dengan metode deskripsi dan analisis interpretatif berkaitan dengan persoalan yang dibahas. Adapun hasil penelitian ini menunjukkan terdapat beberapa jalan mengaktualisasikan moderasi beragama era pandemi ini antara lain, menyeimbangkan teologi, menaati protokol kesehatan, penguatan pengetahuan, mengambil sikap waspada atau mengontrol emosi, dan apabila telah dinyatakan positif hendaknya segera dikarantina.